Hip hemiarthroplasty for fractured neck of femur; a freedom of information study to assess national variation in implant selection and procurement. Issue 6 (December 2019) - Martin, Alexander; Vanhegan, Ivor; Dean, Benjamin
Abstract: Introduction: During 2016, according to the National Hip Fracture Database (NHFD), over 65, 000 patients suffered a hip fracture of which approximately half underwent hemiarthroplasty. Clear guidelines exist on the usage of proven cemented implants. The Getting It Right First Time (GIRFT) Report highlighted the financial implications of 'unwarranted variation' and stressed the importance of rationalising and standardising service provision, in particular implant usage. The primary aims of this study were to investigate the variation in hip hemiarthroplasty implant usage and associated costs. We hypothesised there to be large variation in implants used and procurement costs. Methods: Freedom of Information Requests (FOI) were sent to all 177 hospitals listed in the 2017 NHFD Report as treating hip fracture patients. All hospitals were asked for their most commonly used hemiarthroplasty implant and the cost of this, per patient. Results: One hundred sixty six (94%) responses were received. Eighty four (51%) provided implant name and cost, 78 (47%) provided implant name but refused costs and 4 (3%) refused to provide any details. Nineteen different prostheses were used nationally with 20 hospitals using a non-ODEP (Orthopaedic Data Evaluation Panel) 10A implant. Average total cost was £725.00 (range £71-£1378). Significant cost variation was demonstrated for the same implants; one implant was £978.19 at it's most costly and £285.59 at it's cheapest. Discussion: The aims of this study have been met. We have demonstrated huge variation in the implants used for hip hemiarthroplasty and their costs. Notwithstanding the nuances of departmental procurement processes, the financial implications for this variation are significant. Conclusions: This article demonstrates a requirement for rationalisation of implant usage and procurement in order to potentially improve patient outcomes and provide opportunities for significant cost saving in an already overstretched health service.